An Analysis of Liquidity Position of Indian Steel Industry - Krishna, A. R; Pandey, Shishir (Journal of Commerce and Trade, 2013)
India has emerged as the fourth largest steel producing nation in the world, as per the recent figures release by World Steel Association. Rapid rise in production has resulted in India becoming the 4th largest producer of crude steel and the largest producer of sponge iron or DRI in the world. For a successful working of a business organization, current assets play a vital role. Management of working capital is essential as it has direct impact on efficiency and liquidity. An attempt has been made in this paper to study the financial efficiency and liquidity positions and its impact of Steel industry in India. The study is based on steel Industry represented by Jindal Steel, SAIL and TISCO. In the study Ratio analysis and statistical tools like standard deviation and coefficient of variation have been used to analyze the data.